2003
DOI: 10.1103/physrevb.67.024425
|View full text |Cite
|
Sign up to set email alerts
|

EPR ofFe3+in aLaCaAlO4single crystal: Effect o

Abstract: EPR studies have been carried out on a Fe 3ϩ -doped LaCaAlO 4 single crystal at the X band ͑9.6 GHz͒ at room, liquid-nitrogen, and liquid-helium temperatures to study the effect of substitutional disorder that results when Ca 2ϩ and La 3ϩ ions substitute at the same site in this crystal. The variation of the observed Fe 3ϩ EPR linewidth as a function of the orientation of the external magnetic field with respect to the crystallographic c axis is found to be consistent with that reported previously for the Fe 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, EPR studies on the Cr 3+ ion in EuAlO 3 have been reported [8], as well as those on Gd 3+ in the isostructural LaAlO 3 and YAlO 3 crystals [9,10]. A relevant detailed EPR study of the Gd 3+ ion in monoclinic La 2 Si 2 O 7 and LaNbO 4 crystals, which are also characterized by a low (C S , and C 2 , correspondindly) point symmetry of the Gd 3+ ion and exhibit low-symmetry effects, was reported by Misra and Andronenko [11,12].…”
Section: Was Recently Reported Bymentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, EPR studies on the Cr 3+ ion in EuAlO 3 have been reported [8], as well as those on Gd 3+ in the isostructural LaAlO 3 and YAlO 3 crystals [9,10]. A relevant detailed EPR study of the Gd 3+ ion in monoclinic La 2 Si 2 O 7 and LaNbO 4 crystals, which are also characterized by a low (C S , and C 2 , correspondindly) point symmetry of the Gd 3+ ion and exhibit low-symmetry effects, was reported by Misra and Andronenko [11,12].…”
Section: Was Recently Reported Bymentioning
confidence: 91%
“…Alternatively, for Gd 3+ in La 2 Si 2 O 7 [11], the C S -axis is parallel to the X-axis, so that only those m n b , where m ( n) are odd and negative and n are 2, 4, 6, are non-zero. This is also the case for Gd 3+ in LaNbO 4 and PrNbO 4 [12]. The third 6 case, where C S is parallel to the Z-axis, occurs for Gd 3+ in YAlO 3 [6], where only those m n b , where m ( n) are even and negative and n are 2, 4, 6, describe the low-symmetry.…”
Section: Spin-hamiltonian Parametersmentioning
confidence: 95%
See 1 more Smart Citation